1993+1993•1994-1995•1992=
Răspunsuri la întrebare
Răspuns de
5
1993+1993*1994-1995*1992=
=1993*(1+1994)-1995*1992=
=1993*1995-1995*1992=
=1995*(1993-1992)=
=1995*1=1995
=1993*(1+1994)-1995*1992=
=1993*1995-1995*1992=
=1995*(1993-1992)=
=1995*1=1995
zoicamergeane:
Multumesc
Răspuns de
1
1993+1993*1994-1995*1992=
=1993*(1+1994)-1995*1992=
=1993*1995-1995*1992=
=1995*(1993-1992)=
=1995*1=1995 rezultatul este 1995.
=1993*(1+1994)-1995*1992=
=1993*1995-1995*1992=
=1995*(1993-1992)=
=1995*1=1995 rezultatul este 1995.
Alte întrebări interesante
Geografie,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă